2009
DOI: 10.2353/ajpath.2009.090219
|View full text |Cite
|
Sign up to set email alerts
|

Presenilins Are Enriched in Endoplasmic Reticulum Membranes Associated with Mitochondria

Abstract: Presenilin-1 (PS1) and -2 (PS2), which when mutated cause familial Alzheimer disease, have been localized to numerous compartments of the cell, including the endoplasmic reticulum, Golgi, nuclear envelope, endosomes, lysosomes, the plasma membrane, and mitochondria. Using three complementary approaches, subcellular fractionation, ␥-secretase activity assays, and immunocytochemistry, we show that presenilins are highly enriched in a subcompartment of the endoplasmic reticulum that is associated with mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
318
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(337 citation statements)
references
References 54 publications
17
318
1
1
Order By: Relevance
“…In previous reports, we showed that γ‐secretase activity is localized in MAM (Area‐Gomez et al , 2009) and that alterations in γ‐secretase activity result in the upregulation of MAM function and in increased ER–mitochondria apposition (Area‐Gomez et al , 2012). We now show that the γ‐secretase substrate C99, in addition to its endosomal localization, is also present in MAM domains.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In previous reports, we showed that γ‐secretase activity is localized in MAM (Area‐Gomez et al , 2009) and that alterations in γ‐secretase activity result in the upregulation of MAM function and in increased ER–mitochondria apposition (Area‐Gomez et al , 2012). We now show that the γ‐secretase substrate C99, in addition to its endosomal localization, is also present in MAM domains.…”
Section: Discussionmentioning
confidence: 80%
“…Consistent with the data of others (Das et al , 2016), FL‐APP and BACE1 co‐migrated partially with a marker for endosomes (Rab7), but not with lysosomal, ER‐intermediate, or MAM markers (Fig 2C). Similarly, the APP‐CTFs C83 and C99 co‐migrated with endosomal and lysosomal markers (Rab5, Rab7, and LAMP‐2) (Haass et al , 2012; Das et al , 2016), whereas PS1 co‐migrated with MAM markers, such as FACL4 (Area‐Gomez et al , 2009; Newman et al , 2014; Schreiner et al , 2015). We reasoned that the difficulty in seeing APP‐CTFs and PS1 together was probably due to the rapid cleavage of the CTFs by γ‐secretase once both are in the same compartment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported previously that PS1, PS2, and γ‐secretase activities are highly enriched in the MAM 10 and that ER–mitochondrial communication and MAM function, including phospholipid and cholesteryl ester synthesis, are increased dramatically in presenilin‐mutant and presenilin‐deficient cells and in cells from AD patients 7. Both lines of evidence support the view that PS1 and PS2, in addition to generating Aβ, are negative regulators of MAM function 7 and that these alterations play a critical role in the pathogenesis of the disease (the “MAM hypothesis”) 11, 12.…”
Section: Resultsmentioning
confidence: 92%